Analysis Of The Core Tax Digitalization Innovation System For The World Of Taxation For The Compliance Of Taxpayers Of North Sumatra Province - Maisyura, Dina; Syafina, Laylan; Nurwani, Nurwani (Amkop Management Accounting Review (AMAR), 2025)
Tax as one of the sources of state revenue which of course has great potential in financing national development. However, the problems of the people in North Sumatra arise due to the lack of efficiency in the taxpayer administration system because most people lack access to tax information. Therefore, this study aims to analyze the application of the Core Tax digitalization innovation system in the world of taxation for taxpayer compliance in North Sumatra Province. The study uses a descriptive qualitative approach with data collection techniques through documentation studies, secondary data analysis from DJP reports, and in-depth interviews with key informants, including tax instructors and operational employees of the tax office. Based on the results of the research that has been conducted, it can be concluded that the application of the Core Tax Administration System (CTAS) as a form of digital innovation in tax administration has had a positive impact on increasing efficiency, transparency, and ease of tax services in North Sumatra Province.